Quantitative analysis of ethanol–methanol–water ternary solutions using Raman spectroscopy. Issue 5 (28th May 2019) - Numata, Yasushi; Shinohara, Yuta; Tanaka, Hiroyuki
Abstract: Raman spectroscopy was used for rapid in-situ measurement of alcohols in ethanol-methanol-water ternary systems. Mass fractions of the individual components were determined using calibration curves for binary systems of ethanol-water, methanol-water, and ethanol-methanol. Calibration curves were constructed by calculating the ratio of the Raman peak intensity of a component and that of an external standard (acetonitrile). Assuming additivity of the spectra, simultaneous equations were written, and mass fractions of ethanol, methanol, and water in the ternary solutions were determined by solving the system of equations through calculating an inverse matrix. The relative errors between the mass fractions obtained from the Raman spectra and those obtained from mass measurements were <0.6%.